FENOMENA GERHANA MATAHARI CINCIN DAN KONJUNGSI (Uji Akurasi Awal Bulan Syawal &Dzulqa’dah 1442 H Dalam Perspektif Kriteria 29) - Nihayatur Rohmah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2021)
Abstract The problem in determining the beginning of the month of Kamariyah is very important and needed by Muslims. Moreover, if it is associated with the issue of worship, the accuracy/accuracy in the calculation and determination is a significant thing. Ijtima 'is one of the conditions for the beginning of a new month in the Kamariyah calendar and the existence of a link between the events of the solar eclipse that occurred in June 2021 can be used as one of the parameters in determining the accuracy of the day or date in the kamariyah month. The data processing in this paper uses a qualitative approach in the form of a descriptive narrative by simulating a countdown after knowing the time of ijtima or conjunction and corroborated by the phenomenon of a solar eclipse through the perspective of criterion 29. After determining the 29th date that occurs after sunset, we do not determine the next day's date instead of setting an earlier date. This is because the number of days in the Hijri calendar is 29 days or 30 days. In other words, the 30th may or may not exist. So with simple logic, if the 29th has been set, the previous day must be the 28th. The existence of the 30th is determined by counting backwards from the month after that. Thus, referring to the perspective of criterion 29 and based on the occurrence of an annular solar eclipse on June 10, 2021, which coincides with the occurrence of Ijtima at the beginning of the month of Dzulqa'dah 1442 H, making the determination of the date of 1 Shawwal 1442 H an accurate calculation. Keywords: Ijtima', Eclipse, Criterion 29